NANO FERTILIZER: ITS IMPACT ON CROP GROWTH AND SOIL HEALTH - SIVAKOTI RAMANA, TAPAN ADHIKARI and (The Journal of Research, PJTSAU, 2020)
Recent developments on application of nanotechnology in agriculture, plant mineral nutrition, soil health, and interactions with soil micro-flora directed to sustainable solutions by replacing traditional bulk fertilizers with their nano-particulate counterparts possessing superior properties to overcome the current challenges of bioavailability and uptake of minerals, increasing crop yield, reducing fertilizer wastage, and protecting the environment. Several studies showed that nano-particles of essential minerals and nonessential elements affected plant growth, physiology, and development, depending on their size, composition, concentration, and mode of application. It was reported that nano-particles and nano-tubes in numerous crops like sunflower, common bean, and maize enhanced germination and seedling growth, physiological activities including photosynthetic activity and nitrogen metabolism, mRNA expression and protein level, and positive changes in gene expression, indicating their potential use for increasing crop yields. The creation and improvement of fertilizers at nanoscale dimensions could have a profound impact on energy, the economy and the environment. Speculation not withstanding, the scientific, technical, and agricultural projects linked with nano-fertilizers must include side effects in order to accurately determine progress and shape a sustainable future.